GENDER AND SEASONAL FEATURES OF DEVELOPMENT PROCESS OF PHLEGMON OF MAXILLOFACIAL AREA - K. Vakulenko (Український стоматологічний альманах, 2018)
The article describes the patterns and characteristics of occurrence and course of phlegmon of the maxillofacial region, which are to determine the relationship of gender-seasonal characteristics. Increasing trend in recent years not only to increase the frequency and number of abscesses, but also to increase the number of complications. Complications, many authors attributed to changes in the nature of the disease and, often, it atypia. Noteworthy that most often the main contingent of patients phlegmons a person of working age, ie 20- 40 years of age, they occur most often complications. Therefore, it is advisable to treat cellulitis as one of the leading causes of temporary incapacity, disability and mortality in surgical dental patients. It should be noted, and poorly understood issue of gender characteristics and seasonal occurrence of abscesses maxillofacial area that we believe has its own laws it will study the possibility to specify tactics in a particular case. A retrospective study and analysis of case histories of 280 patients between 18 and 75 years who were treated at the clinic between 2006 and 2008 with a diagnosis of abscess of soft tissues of the maxillofacial area of a particular location. All patients - residents of the city of Kharkiv and Kharkiv region. Dominated by patients under the age of 40 years. Notes the prevalence of odontogenic causes of the inflammatory process in the autumn and winter, more often in men than in women. Noteworthy is the fact that, in general, the highest peak uptake in patients with soft tissue phlegmon of the maxillofacial area in the autumn and winter. Also of interest is a comparison of the treatment periods patients from the time of disease onset. Was more severe in males, it is connected not only with the later treatment, but also with a history of chronic diseases, alcohol and smoking.